2020
DOI: 10.1155/2020/8291413
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic Acid D Protects Human Amniotic Mesenchymal Stem Cells against Oxidative Stress-Induced Senescence through the PERK/NRF2 Signaling Pathway

Abstract: Aging is an important risk factor in the occurrence of many chronic diseases. Senescence and exhaustion of adult stem cells are considered as a hallmark of aging in organisms. In this study, a senescent human amniotic mesenchymal stem cell (hAMSC) model subjected to oxidative stress was established in vitro using hydrogen peroxide. We investigated the effects of ganoderic acid D (GA-D), a natural triterpenoid compound produced from Ganoderma lucidum, on hAMSC senescence. GA-D significantly inhibited β-galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
1
27
1
Order By: Relevance
“…Similarly, extracellular signal-regulated kinase (ERK) and mitogen-activated protein kinases, such as p38, both promote Nrf2 activation and upregulate Nrf2 target genes [ 140 , 141 ]. In particular, p38 phosphorylates Nrf2 at three serine residues (Ser 215 , Ser 408 , and Ser 577 ), facilitating a decrease in Nrf2 nuclear accumulation [ 142 ].…”
Section: Nrf2 Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, extracellular signal-regulated kinase (ERK) and mitogen-activated protein kinases, such as p38, both promote Nrf2 activation and upregulate Nrf2 target genes [ 140 , 141 ]. In particular, p38 phosphorylates Nrf2 at three serine residues (Ser 215 , Ser 408 , and Ser 577 ), facilitating a decrease in Nrf2 nuclear accumulation [ 142 ].…”
Section: Nrf2 Phosphorylationmentioning
confidence: 99%
“…Some triterpenoids also have obvious antioxidant and antiaging activity. For instance, Xu et al demonstrated that ganoderic acid D exhibits potent antisenescence effects against H 2 O 2 -induced premature senescence of human amniotic mesenchymal stem cells through the activation of PERK/Nrf2 signals [ 141 ]. Additionally, Lefaki and colleagues demonstrated that 18 α -glycyrrhetinic acid can activate the Nrf2/SKN-1 pathway against DNA damage [ 207 ].…”
Section: Antioxidant Ingredients In the Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…An antiaging action of G . lucidum was shown in a recent study [ 26 ] by assaying the effects of ganoderic acid D on oxidative stress-induced stem cell senescence, using an H 2 O 2 -induced stem cell senescent model using human amniotic mesenchymal cells (hAMSCs) with a high expression of β-galactosidase, a senescence-associated marker. Ganoderic acid D inhibited the generation of reactive oxygen species (ROS) and senescence-associated markers, such as β-galactosidase, p21, and p16INK4a, and enhanced telomerase activity through the activation of the PERK/NRF2 signaling pathway.…”
Section: Bioactive Compounds In Medicinal Mushrooms: Effects and Mmentioning
confidence: 99%
“…Oxidative stress preconditioning could protect the MSCs vitality through activating the Nrf2 pathway and upregulating its downstream target of the superoxide dismutase, catalase, and HO-1 ( Zhang F. et al, 2019 ). Moreover, many strategies had been explored to avoid cell apoptosis and senescence initiated by oxidative stress, including pioglitazone, vaspin, ganoderic acid D, and vitamin E ( Bhatti et al, 2018 ; Hu et al, 2019 ; Zhu et al, 2019 ; Xu et al, 2020 ). Taken together, before MSCs could be reliably and effectively used as hemorrhage stroke therapy, it is necessary to better understand the multiple microenvironmental regulatory mechanisms driving transplanted MSCs to form repair effect.…”
Section: Challenges Of Ich Microenvironment On Mscs Therapymentioning
confidence: 99%